Analisis Faktor-Faktor yang Mempengaruhi Tingkat Pendapatan Petani Garam di Desa Tendakinde Kecamatan Wolowae Kabupaten Nagekeo - Mengi , Adrianus; Leha, Ernesta; Nona, Reyna Virginia (JURNAL EQUILIBRIUM, 2022)
This research aims to determine the factors that influence the income level of salt farmers in Tendakinde Village, Wolowae District, Nageke Regency. The research method used is a quantitative approach to see whether there is an influence of capital, labor, technology and land area on the income of salt farmers. Data collection techniques in this research are observation and questionnaires. Data analysis uses multiple linear regressive analysis tools. The theory used in this research is income theory. The research results show that first, the capital variable has a positive and significant effect on the income of salt farmers in Tendakinde Village. This is proven by the results of the significant individual parametric t test where the calculated t value > t table (9.011> 1.699). Second, labor has a positive and significant effect on the income of salt farmers with a value of t> t table (9.342> 1.699>. Third, technology has a positive and significant effect on the income of salt farmers with a value of t> t table (7.466> 1.699). Fourth, Land area has a positive and significant effect on the income of salt farmers with t count > t table (8.902 > 1.699).